2015
DOI: 10.1155/2015/587131
|View full text |Cite
|
Sign up to set email alerts
|

Human Coinfection withBorrelia burgdorferiandBabesia microtiin the United States

Abstract: Borrelia burgdorferi, the causative agent of Lyme disease, and Babesia microti, a causative agent of babesiosis, are increasingly implicated in the growing tick-borne disease burden in the northeastern United States. These pathogens are transmitted via the bite of an infected tick vector, Ixodes scapularis, which is capable of harboring and inoculating a host with multiple pathogens simultaneously. Clinical presentation of the diseases is heterogeneous and ranges from mild flu-like symptoms to near-fatal cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 62 publications
1
25
0
Order By: Relevance
“… 74 Any patient who complains of unexplained fevers, day and night sweats, chills, flushing, an unexplained cough, and shortness of breath (air hunger), which are questions number 1 and number 22 (Section 1 of the HMQ), may also have a concomitant infection with babesiosis. 75 – 77 A Babesia panel approach with a Giemsa stain, Babesia titers (IFA) for multiple species of Babesia ( Babesia microti , Babesia duncani [WA-1, Babesia divergens and Babesia sp. EU1 ]), with PCR [61] and FISH testing, may help to establish the diagnosis 78 in the United States and Europe, 78 while ruling out other causes of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 74 Any patient who complains of unexplained fevers, day and night sweats, chills, flushing, an unexplained cough, and shortness of breath (air hunger), which are questions number 1 and number 22 (Section 1 of the HMQ), may also have a concomitant infection with babesiosis. 75 – 77 A Babesia panel approach with a Giemsa stain, Babesia titers (IFA) for multiple species of Babesia ( Babesia microti , Babesia duncani [WA-1, Babesia divergens and Babesia sp. EU1 ]), with PCR [61] and FISH testing, may help to establish the diagnosis 78 in the United States and Europe, 78 while ruling out other causes of these symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There, B. microti shares its vector host with Borrelia sp., the causative agent of Lyme disease. Thus, it has been reported that some Lyme disease patients also suffer from human babesisosis (Diuk-Wasser, et al, 2016, Knapp and Rice, 2015). …”
Section: Inhibition Of Apicomplexan Parasite Growth and Replicatiomentioning
confidence: 99%
“…A large panel of tick-borne diseases, which affect both humans and wild mammals, can result from the transmission of several pathogens including bacteria, viruses, and protists. It is known that ticks can harbor and co-transmit multiple pathogens (Knapp and Rice, 2015 ). Malaria and tick-borne diseases overlap in many African regions, therefore co-infections in Anopheles mosquitoes may be possible after successive or concomitant infectious blood meals on hosts carrying both micro-organisms.…”
Section: Malaria and Bacteria Co-infections In Mosquitoesmentioning
confidence: 99%